Interpretation of Bi Al-Ra’yi Madrasah Tafsīr Makkah - Sufyan Syafii; M. Mizan Sya’roni (Eduvest - Journal of Universal Studies, 2021)
The interpretation of the Al-Qur'an does not only come from narrations, but also from the ratio or ijtihad, and intuition or inspiration whose methods are difficult to find, because they are transcendent. This explanation is the background of the author who will conduct the research with the aim of knowing the practice of the interpretation of the Al-Qur'an carried out by Tabi'in. It also shows the fact that Tabi'in uses ratio in interpreting the verse. The research method used in this research is qualitative research with the type of library research. This research discussion uses descriptive-analysis method. The results of this study conclude that in terms of term, the tendency of the tafsir book to not reach certain disciplines, is only limited to geographic influences and is thick with the nuances of the interpretation of the teacher, namely ibn abb's. There are at least 23 bi al-Ra'yi interpretations of Mujâhid's tafsir, which are also agreed upon by several scholars, both from the tabi'in and commentators, but not all of them are the same as the opinion of Ibn Abbâs as his teacher. Of the 23 bi-rayi interpretations, 15 of them are different from Ibn Abbas's interpretation and 8 of them have similarities with Ibn Abbas and are classified into 4 parts, namely: Tafsîr bi al-Ra'yi bi al-Qiyas, Tafsîr bi al-Ra'yi bi al- Qisshah, Tafsîr bi al-Ra'yi bi al-Lughah, Tafsîr bi al-Ra'yi bi al-Dhamir.